P-134 Hospice and dementia care: innovation and collaboration. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Watson, Heather
Abstract : Background: While few people challenge the belief that dementia is a life-limiting illness, it has struggled to be accorded the same degree of service provision within the palliative care domain as other life-limiting illnesses (Hospice UK, 2015). There are differing reasons for this ranging from the historical focus of hospice care which has traditionally not included individuals with a dementia diagnosis, to concerns about knowledge and skills of staff, and resource implications of an extending service. Key Issues: Referrals to the hospice for people with dementia are generally low. Anecdotal evidence from discussions with local dementia services highlighted that many staff are aware of the role of hospice care in dementia. The Hospice Dementia Working Group therefore reviewed its provision of end of life care for people with dementia identifying areas for development mapped against the Southwest Hospital Standards in Dementia Care. Method: Following the review a dementia strategy was developed with six key actions for the next year: To develop a Dementia friendly environment; Workforce dementia awareness training for all staff; The rollout of a training programme for dementia care professionals to support end-of-life care locally, raising awareness of the role of hospice care; Representation at local dementia strategy groups to contribute an end of life perspective to dementia service plans; To build collaborative and mutually supportive ways of working with local dementia services; To engage with the community in the development of Dementia Action Alliances. Conclusions: Key learning from this process is that hospices need to be proactive to ensure their service is responsive to people with dementia. Community engagement and cross organisational working is crucial to this with the Hospice being involved in dementia service development and highlighting their commitment to equality of access for people with dementia and their families.